Simulation Model to Analyze the Effect of Planting Schedule and Predict the Productivity of Red Chilies in Pagar Alam City - Nur Annissa; . Impron (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2017)
The city of Pagar Alam, South Sumatra is at an altitude of 600-2700 masl. The city has climatic and soil condition suitable for red chili plants (Capsicum annuum L.) that have high economic value. However, the fluctuating amount of red pepper production throughout the year can lead to excess or lack of availability of red chili in the market. This research was conducted to use a crop model to simulate the development, growth, and production of red pepper plant. This model used daily weather as input to simulate daily biomass (kg/ha) components of roots, stems, leaves, and fruits. Comparison of fruit components from simulation with field data taken at three areas in Pagar Alam city showed model accuracy of 76% for Koramil area, 91% for Perandonan area, and 85% Pagargading area. The simulation model result show that the average monthly chili productivity varies; highest of 3376 kg/ha if planting is done in October, and the lowest of 2828 kg/ha if planting is done in February.